Visual Features for Lithuanian Phone Recognition - Tamulevičius, G.; Eringis, D. (Elektronika ir Elektrotechnika, 2013)
Paper presents visual features for speech recognition. Visual speech recognition can be applied as support for acoustical recognition process or as stand-alone speech recognition approach in the case of absence of acoustical data. Geometrical features of speaker‘s lips are presented. Statistical analysis of feature values enabled us to select individual feature for each analyzed phone and one combined feature for all phones. The discriminative power was tested using Bayes classification rule. 4th order analysis enabled us to recognize phones with the average rate of 60.3 %, the highest recognition rate of 81.3 % was achieved identifying phone [o].DOI: http://dx.doi.org/10.5755/j01.eee.19.5.1724